Pengaruh Kualitas Pelayanan terhadap Tingkat Kepuasan Nasabah Kredit Pada PT. Bank BTPN Syariah Cabang Belitang II - Aras Tulip; Tutik Pebrianti; Vivin Afini; Arubina Bangsawan; Zein Ghozali (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2021)
This study aims to determine how much influence service quality has on customer satisfaction levels at PT. Bank BTPN Syariah Belitang II Branch, through indicators of service quality variables.The sample used in this study was the customers of Bank BTPN Syariah Belitang II Branch as many as 92 respondents, the data were obtained through a questionnaire. The method used in taking this sample is the probability sampling technique; simple random sampling. The analytical method used is simple linear regression analysis using the SPSS for Windows version 25 program.The results of testing the hypothesis, from the statistical test results it can be seen that tcount obtained a value of ttable with a value of 9.622> 1.662 and a sig. < 0.05 with a value (0.000 <0.05) thus it can be concluded that there is a significant influence of the service quality variable on the level of customer satisfaction. The X coefficient value is 0.629 indicating that if the value of the independent variable (service quality) is 1, then the customer satisfaction level will increase by 0.629. If it is assumed that if the company uses Service Quality (X), the Customer Satisfaction Level (Y) will increase by 62.9%.